Análise do ganho de resistência em vigas de concreto armado submetidas à flexão reforçadas com manta de fibra de carbono - Plácido, Carlos Eduardo (2014)
The construction sector has experienced an odd moment, since this is fastpaced. The development of concrete technology, construction techniques and implementation of computer systems for the preparation of structural design, have enabled them to envisage more clearly the behavior of the structure. Thus, structures with thinner structural elements are being built, thus gluing the structure in a higher degree of risk for the development of pathologies. With the need of repairs to heritage sites in Europe, the durability of bridges in North America, and even caused earthquakes in Japan, emerged unconventional methods of repair and reinforcement structures. One method used is carbon fiber, because by presenting quick and easy application, high tensile strength, compression, and shear, and also have the characteristic low specific weight. Due to great demand for repaired and structural reinforcements, a study to better ensure design engineers is required. This study aims to measure the increase of resistance generated by the application plaid carbon fiber reinforced concrete beams. This strength gain was done through mechanical tests. The results showed a large increase of resistance in structural elements, showing that the blanket of carbon fiber is efficient.